Cataclysmic variable stars: photometry of V893 Sco star and spectroscopy of HS 0220+0603 star - Cori, W (2018)
This work was supported by Convenio 102-2015 Fondecyt - Cienciactiva (OAUNI project, P.I. Antonio Pereyra) and Convenio 168-2015 UNI-MINEDU-CONCYTEC (doctorate scholarship for W.C. at Universidad Nacional de Ingenier´ıa). We thank Instituto Geof´ısico del Per´u for lodging at Observatorio de Huancayo during photometric observations at OAUNI and Grupo Astronom´ıa members for their help on these observations. Spectroscopic part of this work was based on observations made with ESO Telescopes at the La Silla Paranal Observatory under program ID 074.D-0657(A). This research has made use of the Spanish Virtual Observatory (http://svo.cab.inta-csic.es) supported from the Spanish MINECO/FEDER through grant AyA2014-55216. We also thank to the editors, Ener Salinas, Harold Blas and Rosendo Ochoa, for their useful suggestions and corrections.